The New Bridge of Ronda (Spain): History of the construction of a landmark in the development of this city - Daniel Torres-Blanco; M. Carmen Ladrón-de-Guevara-Muñoz; Rafael Enrique Hidalgo Fernández (Frontiers of Architectural Research)
The municipality of Ronda, in Spain, has a rich architectural heritage, treasured by its inhabitants over the centuries. Among its numerous buildings of great heritage value, one stands out: the monumental bridge that rises above the precipice of the plateau on which this city sits. It is known as the New Bridge. This unique 18th-century engineering work favoured the expansion and growth of Ronda's population, also affecting its urban development. Currently, it continues to serve as a link between the original city centre and its expansion areas beyond the walls. This research addresses the reasons why this bridge was constructed, as well as the circumstances that marked its different construction phases. In addition, different hypotheses are put forward on how its physiognomy might have been, in the case that each of the different projects proposed for the bridge had been carried out in its entirety. All of this has led to the conclusion that the morphology of this bridge was not the result of a single design, but rather responds to the various modifications made during its construction.